The Influence of Offering Equity, Brand Equity, and Relationship Equity on Customer Satisfaction and Customer Loyalty - Awalludin, Awalludin; Heikal, Jerry (International Journal of Management and Business Applied, 2024)
The rapid growth of the information technology industry has driven the demand for high-quality IT training. Intensive bootcamp IT programs have increasingly become the primary choice for individuals seeking to enter this industry. Through effective IT bootcamps, individuals can acquire skills that align with the rapidly evolving job market demands, while organizations can attract digitally skilled talent ready to face the challenges of Industry 4.0. As the demand for IT training increases, so does the number of IT bootcamps offering a variety of educational products to meet labor market needs. One of the prominent providers is Hacktiv8 Indonesia. Since its establishment in 2016, Hacktiv8 has faced numerous challenges, one of which is maintaining customer engagement to ensure continued use of its services. This research aims to analyze the influence of Offering Equity, Brand Equity, and Relationship Equity on Customer Satisfaction and Customer Loyalty among participants in Hacktiv8 Indonesia’s IT Bootcamp, with a focus on a case study of Hacktiv8. The research method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS), and the data was collected through an online survey of 150 participants who are currently enrolled or about to enroll in Hacktiv8’s IT Bootcamp. The analysis results are expected to provide better insights into the factors affecting customer satisfaction and loyalty within the context of IT bootcamp training. The practical implications of these findings are anticipated to assist educational and training institutions in enhancing their offering strategies, brand management, and customer relationship building to improve customer satisfaction and loyalty in the future.